2022
DOI: 10.1038/s41598-021-04342-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and prognosis for male breast cancer compared to female breast cancer

Abstract: Male breast cancer (MBC) is rare. Due to limited information, MBC has always been understudied. We conducted a retrospective population-based cohort study using data from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) program. The clinical and biological features of female breast cancer (FBC) patients were compared with MBC patients. Cox regression models and competing risks analyses were used to identify risk factors associated with cancer-related survival in MBC and FBC gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 31 publications
(23 reference statements)
6
29
0
Order By: Relevance
“…In a comparison between prognostic factors studied in both sexes, Yao [ 98 ] found that as opposed to FBC patients, MBC patients were discovered at more advanced TNM stages, with higher tumor grades, and with a greater proportion of hormone receptor-positive tumors. In addition, the locations of breast tumors differed significantly between males and females, and longer survival rates were found in women.…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison between prognostic factors studied in both sexes, Yao [ 98 ] found that as opposed to FBC patients, MBC patients were discovered at more advanced TNM stages, with higher tumor grades, and with a greater proportion of hormone receptor-positive tumors. In addition, the locations of breast tumors differed significantly between males and females, and longer survival rates were found in women.…”
Section: Resultsmentioning
confidence: 99%
“…As of August 2022, there were only eight actively recruiting trials specifically for male breast cancer in the world, 8 and consequently, findings from female breast cancer trials are used to inform treatment of male breast cancer. This is especially concerning because, given increasing use of targeted therapies and the differences in male and female breast cancer biology 9 , 10 , results from trials comprised of women may not be generalizable to men. Given that men with breast cancer, compared to women, have 19% higher overall mortality 11 , it is clear that clinical trials in this population are sorely needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, triple-negative breast cancer in male patients is likely to be at a more advanced stage at the time of diagnosis, often with worse outcomes than in women. In addition, cancer treatments in men are commonly extrapolated from those used to treat postmenopausal women with breast cancer without evidence to support this extrapolation from women to men [4]. Studies Male Murine Breast Cancer World J Oncol.…”
Section: Introductionmentioning
confidence: 99%
“…However, triple-negative breast cancer in male patients is likely to be at a more advanced stage at the time of diagnosis, often with worse outcomes than in women. In addition, cancer treatments in men are commonly extrapolated from those used to treat postmenopausal women with breast cancer without evidence to support this extrapolation from women to men [ 4 ]. Studies addressing the biology and management of breast cancer in men (e.g., studies that correlate prognostic factors with treatment outcomes) are limited, and often lack statistical power [ 2 , 5 - 7 ]; data about risk factors, optimal treatment, and short-term and long-term outcomes in men are also unknown [ 8 ].…”
Section: Introductionmentioning
confidence: 99%